Democratic inclusiveness, climate policy outputs, and climate policy outcomes. Issue 7 (9th November 2016) - Böhmelt, Tobias; Böker, Marit; Ward, Hugh
ABSTRACT: In an ideal inclusive political system, all citizens are equally able to influence and challenge policies. We focus on how inclusiveness affects climate policies and outcomes. We argue that more inclusive systems should produce more policies in response to environmental threats and should have better outcomes. We test these hypotheses using panel and cross-sectional data relating to climate policy outputs and outcomes. The results suggest that inclusiveness is positively associated with policy outputs, but probably not with lower emissions of greenhouse gases. This pattern may relate to a lack of deliberation in systems, which are relatively inclusive in the narrower sense of pluralist democratic theory.